DEVELOPING A MATHEMATICAL MODEL TO DETERMINE THE STRENGTH OF SPLICED LATHS MADE FROM POST-CONSUMER WOOD FOR ROOF STRUCTURES IN BUILDINGS - Haida , С.; Udovytskyi , О.; Rutkovska , І.; Salabai , Р.; Salabai , І. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The article presents a study on the bending strength of finger-jointed laths made from reused wood (RW) for roof structural applications. The relevance of this research lies in promoting resource-efficient technologies and the principles of the circular economy in construction. The variability of mechanical properties in secondary timber creates challenges in predicting its strength performance. To quantify the influence of geometric parameters – lath width (B) and finger length (L) – on bending strength, experimental tests were performed, and a second-order two-factor regression model was developed. The model revealed a statistically significant effect of both factors and confirmed a synergistic interaction: the bending strength increases when both width and finger length grow simultaneously. The optimal parameters achieving maximum strength (79.83 MPa) are B=64 mm and L=24 mm. It was demonstrated that reused wood can be effectively transformed into full-length structural elements with strength exceeding 70 MPa, meeting the normative requirements for roof load-bearing members. The practical significance of the study lies in enabling optimization of production parameters for finger-jointed elements, improving material utilization efficiency, and reducing production costs. The recommended parameter ranges – lath width 56–64 mm and finger length 18–24 mm – can be applied in manufacturing standards, technical specifications, and process charts for the woodworking industry. The results contribute to sustainable and resource-efficient timber construction, reducing environmental impact and establishing a foundation for further studies on the durability and long-term performance of reused-wood joints.